Phase diagrams of a CTAB/organic solvent/buffer system applied to extraction of enzymes by reverse micelles - Feitosa, E. [UNESP]; Catelam, K. T. [UNESP]; Hasmann, F. A.; Johansson, Hans-Olof [UNESP]; Roberto, I. C.; Pessoa, A. (Elsevier B.V., 2008)
A partial pseudo-ternary phase diagram has been studied for the cethyltrimethylammonium bromide/isooctane:hexanol:butanol/potassium phosphate buffer system, where the two-phase diagram consisting of the reverse micelle phase (L-2) in equilibrium with the solvent is indicated. Based on these diagrams two-phase systems of reverse micelles were prepared with different compositions of the compounds and used for extraction and recovery of two enzymes, and the percentage of enzyme recovery yield monitored. The enzymes glucose-6-phosphate dehydrogenase (G6PD) and xylose redutase (XR) obtained from Candida guilliermondii yeast were used in the extraction procedures. The recovery yield data indicate that micelles having different composition give selective extraction of enzymes. The method can thus be used to optimize enzyme extraction processes. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Phase diagram; Liquid-liquid extraction; reverse micelles; CTAB; Enzyme; Glucose-6-phosphate dehydrogenase; xylose redutase